Pelatihan Pembuatan Simulasi IoT Smart Home dengan Cisco Packet Tracer di SMK Budi Agung Medan - Labuan Nababan; Jane Elnovreny; Lamtiur Sinambela; Andrian Syaputra (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The use of technological tools in this day and age is no longer a new thing for society, where children, adolescents, adults and even the elderly are common and even have it. The use of this technology is one way to facilitate work quickly that can be done remotely. In this case, sometimes we as a society or as students can only use it without knowing how to make it. Making this IoT-based application can be used to deepen students' knowledge about the process of making and implementing the Internet of Things. IoT is a design, namely an object that has the ability to transmit data through the internet membrane so that the assistance of computers and users is not required. One example of its use in everyday life is the operation of IoT Smart Home, Smart city and others. an example of the Internet of Things smart home that connects electronic devices, such as turning on and off lights, fans, air conditioners, and opening or closing doors remotely via the internet at home. while examples of smart city implementation are E-Tilang, Traffic Light. Here the author volunteered to conduct training on using the Cisco Packet Tracer application in training on making the Internet of Things to turn on electronic devices remotely, to increase students' knowledge as a community service program. Through training for SMK Budi Agung Medan students, it is hoped that they can take advantage of the Cisco Packet Tracer application to improve science and technology in the field of IoT and as a means of the learning process. Budi Agung Medan Vocational School is one of the SMKs located at Jl. Platina Raya No.7, Rengas Island, Medan Marelan District, Medan City.